Quantum Cryptography Simulation of Entanglement and Quantum Teleportation - Brahim Ouchao (Computer Sciences & Mathematics Forum, 2023)
The objective of this article is to present a simulation of quantum information. We take advantage of quantum entanglement to ensure the spontaneous transfer of a state from one qubit to another similar qubit. Similarly, the principle of quantum teleportation is conceived in the application; it is not about transfer of matter, but of information. Indeed, two systems already exist, and at the end of the teleportation, the process is destructive—the first system will no longer be in the same state as the initial state and the second system takes the state of the first, which does not contradict the no-cloning theorem.